Applying Ethical Principles When Discussing Alcohol Use During Pregnancy. (7th September 2020) - Edwards, Alexandra; Kelsey, Beth; Pierce‐Bulger, Marilyn; Rawlins, Susan; Ruhl, Catherine; Ryan, Sharon; King, Diane K.
Abstract: Over the past 2 decades, more women in the United States are engaging in excessive alcohol use, including women of reproductive age. Consuming alcohol in amounts greater than recommended limits is associated with an increased risk for adverse health effects, such as breast cancer, hypertension stroke, spontaneous abortion, and infertility. No safe time, safe amount, or safe type of alcohol to consume during pregnancy has been identified. Contradictory beliefs about alcohol use, fear of stigmatization, and potential legal consequences can provide challenges for health care providers who communicate these risks to clients. Health care providers can help to prevent alcohol‐related health issues, including alcohol‐exposed pregnancies, by providing their clients with factual information about alcohol and health and client‐centered options for reducing their health risks. Clinicians can use alcohol screening and brief intervention as a framework for applying the ethical principles of autonomy, veracity, beneficence, and nonmaleficence when talking with women in ways that are nonstigmatizing and supportive to help reduce their health risks and prevent alcohol‐exposed pregnancies.